Le storie e la memoria - Delle Donne, Roberto (Reti Medievali E-Book, 2002)
This book is a collection of contributions by the Italian scholarship fellows at the Deutsches Historisches Institut of Rome over the last decade. It is intended as a tribute to one of the leading mediaevalists at international level, a scrupulous and sensitive scholar of Italian history. Over and above all this, it is a sign of gratitude from the young academics who have been able to consolidate their research thanks to such scholarships. Consequently the 14 contributions that make up the book do not share the academic orientation of any particular school, but range over various research sectors and different chronological periods.